Development of an Inquiry Stance? Perceptions of Preservice Teachers and Teacher Educators Toward Preservice Teacher Inquiry in Dutch Primary Teacher Education. (May 2022) - van Katwijk, Lidewij; Jansen, Ellen; van Veen, Klaas
This study aims to gain insight into the perceived purpose and value of preservice teacher inquiry in Dutch primary teacher education by teacher educators and preservice teachers at the undergraduate level; it also assesses the implementation of teaching and learning activities, and learning outcomes associated with teacher inquiry. In the Netherlands, inquiry competence in primary teacher education develops over a 4-year period, resulting in students' completion of capstone projects using practitioner inquiry. The authors combine a survey with focus groups of teacher educators and preservice teachers from eight institutes. They find differences between preservice teachers' perceptions of the implementation of inquiry competence and teacher educators' visions and perceptions of such implementation. All participants, students and educators, believe inquiry to be valuable and perceive learning outcomes of inquiry to be enriching, yet about half of the preservice teachers do not to expect to undertake inquiry in their future teaching jobs.